An Emerging Market: The Impact of User Selection on the Decision-Making Behavior of Mobile Medical Businesses in China - Xu, Xinglong; Wei, Jiajia; Zhou, Lulin; Antwi, Henry Asante (Frontiers in Psychology, 2022)
Background: User selection is an important guarantee for the sustainable development of mobile medical. Under the background of increasingly fierce competition, the decision-making behavior of mobile medical businesses will directly affect the choice of behavior of users. Methods: This paper constructs the decision-making behavior model of mobile medical business based on the user choice, and adds the role of people in Government. It uses the game method to explore the decision-making behavior relationship among the government, mobile medical business and users. Finally, it makes an example analysis an empirical analysis is conducted to demonstrate the influence of different parameter changes on the results. Results: The results show that in the absence of government intervention, users' choice of filtering information will create a bad environment for mobile medical businesses, and further will be reduced, and the expected utility of businesses will not be affected caused a reduction in expected utility of businesses. Similarly, Government regulations can effectively improve the mobile medical environment and enhance the expected utility of mobile medical businesses. Conclusions: The government needs to formulate relevant laws and regulations to ensure the orderly operation of mobile medical market and strengthen government supervision. It is necessary to conduct publicity and education to protect the fundamental interests of users and businesses.